Dukungan Pelayanan dengan Pemenuhan Kebutuhan Spiritual Pasien di Ruang Perawatan Kritis - Yustilawati, Eva; Amal, A.Adriana; Khotimah, Nurul Khusnul; Rosdatun, Rosdatun (An Idea Health Journal, 2025)
Fulfillment of patients' spiritual needs is crucial in the nursing care process. Therefore, nurses, as the front line in providing nursing care, need to perform care holistically, including biological, psychological, social, and spiritual needs of patients. The purpose of this research is to determine the factors related to the fulfillment of patients' spiritual needs in the critical care unit of Labuang Baji Hospital, Makassar. The method used is quantitative with a cross-sectional approach. The population in this study is 63 respondents, consisting of 56 samples, using a cluster random sampling technique. The results of the study, using the Spearman rho test, obtained a p-value of 0.014, which means that the better the service support, the better the fulfillment of patients' spiritual needs in the hospital. To ensure the fulfillment of patients' spiritual needs, service support must be improved. Additionally, spiritual care training will enhance the soft skills of nurses in critical care in fulfilling spiritual needs